IMPLEMENTASI PENDEKATAN BERMAIN DALAM PEMBELAJARAN PJOK TERHADAP HASIL BELAJAR SISWA - Syaqiq Qukhoerulloh, - (2023)
This study aims to determine how the implementation of the play approach in physical education and sport (PJOK) learning on student learning outcomes. The method in this study used an experimental method with a One Group Pretest-Posttest Design research design. The instrument used is a student learning outcomes assessment instrument that refers to learning devices in the form of a Learning Implementation Plan or RPP to measure learning outcomes in affective aspects, cognitive aspects and psychomotor aspects. The population in this study were VII grade students of SMP Kartika xix-2 Bandung, the sampling technique used was Simple Random Sampling, so of the four classes obtained VII D class as the research sample. Data analysis using Paired sample t-test obtained t-count (25.070) > t-table (2.064), and significance of 0.00 <0.05. So it can be concluded that the implementation of the play approach has a significant effect on student learning outcomes in affective aspects, cognitive aspects and psychomotor aspects.